(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
This paper focuses on the sedimentological characteristics of the basal mudstone-dominated deposits of the upper Lumbrera Formation, the uppermost unit of the Salta Group (Turner, 1959) (Fig. 1a) exposed in the El Simbolar and Juramento River sites, in the Salta province (Fig. 1b). At El Simbolar, a rich vertebrate fauna and a dated volcanic tuff (i.e., 39.9 Ma, U/Pb method) (Fig. 2) constrain a middle Eocene age for this unit (del Papa et al., 2010). On the bases of macro and microfacies descrip- tions, combined with petrographic, grain-size, and mineralogical studies, we interpret depositional pro- cesses and discuss a possible eolian origin for the fine-grained sediments and the paleogeographic scenario. The upper Lumbrera Formation is a thick unit (100-270 m) with blanket-like geometry dominated by reddish siltstones and sandy siltstones (Fig. 3a). The dominant sedimentary features are bioturba- tion, decolorized halos, desiccation cracks, carbo- nate nodules and pedological structures (Fig. 3 b-d). In the lower part of the unit there is a 2-3 m thick interval of fine-grained laminated sandstones and heterolithic deposits, consisting of wavy and lenticular bedding (Fig. 3c,e). Five sedimentary facies were identified: 1) Bio- turbated siltstone, 2) Calcareous siltstone, 3) White fine-grained sandstone, 4) Heterolithic facies and 5) Volcanic tuff. 1) Bioturbated siltstone facies: this is a fine- to coarse-grained siltstones with subordinate percentage of clay, micro spar and hematite (Fig. 4a); some levels present volcanic shard fragments (Fig. 4b). This facies presents clay and hematite coating pores, cracks and grains. In some parts, it is possible to observe the preferential orientation of clays, interpreted as microslickensides (Fig. 4c) and delineating aggregates with low to moderate birefringence of the micro-mass. Ferric oxides minerals form nodules, concretions (Fig. 4d), and pendant cements. Also, pisolites structures floa- ting in the fined-grained matrix are observed (Fig. 4e). The presence of chambers and tubes with open pores or filled with spar cement (Fig. 4f) are common structures. 2) Calcareous siltstone facies is characterized by the relative increment in the calcite content (Fig. 4g,h), and the moderate to high birefringence of the micro-mass (Fig. 4g). 3) White fine-grained sandstone facies: consists of fine- to very fine-grained feldspathic arenite. The beds are tabular, with internal horizontal lamination and wave ripple cross-lamination capped by mudstone drapes (Fig. 3c). 4) Heterolithic facies: consists of alternation of fine-grained sandstones and mudstones levels showing wavy and lenticular bedding (Fig. 3c,e). Vertical burrows and ferruginous nodules are also observed. 5) Volcanic tuff facies: consists of whitish, 25 cm thick beds composed of crystal tuff. The sedimentary features described in the upper Lumbrera Formation allow to reconstruct vegetated plain paleoenvironments dominated by fine-grained sedimentation from setting and sporadic low-energy water flows that temporally flooded some topographic depression. The presence of micro-fabric, micro- structures and features such as birefringence, aggre- gates, cutans, glaebules, pisolites, crystalarias, root traces, and bioturbation are all indicative of paleosols development. Grain-size analysis show silt as the main fraction (3.9 - 63 µm) with up to a 50% of volume in weight, following by fine-grained sand (63 - 500 µm) (ranging 5.7 and 43.22%) and with 20% of clay fraction (< 3.9 µm) (Table 1). The grain-size curves (Fig. 5a) display a bimodal distribution pattern where the main mode is fine silt (7.8 - 15.6 µm), while in only three samples the modes are very fine sand (63 - 125 µm). The secondary observed mode is variable but in all cases is represented by very fine sand. The median of the analyzed samples are medium silt fraction (15.6 – 31 µm) and fine silt (7.8 - 15.6 µm) (Table 2). The samples are sandy siltstones and siltstones (Fig. 5b) according to Folk´s (1974) textural classifi- cation. Moreover, the DRX diagrams (Fig. 6) perfor- med on whole rock remark the mineralogical homogeneity along the studied section. Two minera- logical groups are identified: 1) detrital or allogenic, composed of quartz, plagioclase and illite/muscovite, and 2) autigenic, including calcite, analcime and hematite. One of the key features to identify the loess is the dominant presence of silt particles (Pye, 1987, 1995). Although a “typical loess” is characterized by more than 80% of silt (Pye, 1987), this percentage is variable, and sometimes samples are classified as loess deposits with more than 50% of silt and important percentages of sand (sandy loess) and clay (clayey loess) fractions (Pye, 1995). On the base of the sedimentological studies presented here we interpret the deposits of upper Lumbrera Formation as sandy loess. Our results are compared with similar deposits from Quaternary loess (Pampean loess, Córdoba province) and modern dust (Marco Juarez, Córdoba province) (Gaiero et al., 2013). Figure 7 shows the existence of similarities between the mean grain-size distributions of the studied materials. We interpret that the source of loess particles is associated with the proto-Andes that was under uplift during the Eocene-Oligocene, contempora- neously with the upper Lumbrera sedimentation. Furthermore, we consider the existence of a secondary source probably linked to material derived from the volcanic arc, active in Chile at that time.